Mesenchymal stromal cell therapy for feline chronic gingivostomatitis: Long term experience - Soltero-Rivera, Maria; Hart, Sterling; Blandino, Andrew; Vapniarsky, Natalia; Arzi, Boaz (Frontiers in Veterinary Science, 2023)
The long-term safety and efficacy of mesenchymal stromal cells (MSC) therapy for feline chronic gingivostomatitis (FCGS) was retrospectively evaluated. A review of medical records, histopathology, and the Stomatitis Activity Disease Index (SDAI) of thirty-eight client-owned cats that received MSC therapy was performed. Long-term follow-up ranged from two to nine years post-MSC treatment. Correlations of the long-term follow-up success rates with SDAI pre- and post-therapy and allogeneic versus autologous treatments were conducted. Finally, a client survey on quality-of-life following treatment, side effect occurrence, brief medical history, and overall treatment satisfaction was performed. The overall positive response rate to MSC treatment was 65.5%, with 58.6% of cats exhibiting permanent improvement or cure. Adverse effects occurring during or immediately after treatment were noted in 34.2% of cases, the majority being transient, self-resolving transfusion-like reactions. No long-term adverse events were noted. No significant correlation in outcome was detected between allogeneic and autologous MSC treatment (p=0.871) or the severity of the SDAI at entry (p=0.848) or exit (p=0.166), or the delta SDAI between entry and exit (p=0.178). The status six months (none to partial improvement vs. substantial improvement to resolution) post-therapy was a predictor of long-term response (p-value <0.041). Most clients were satisfied with the treatment and outcomes, with 90.6% willing to pursue treatment again, given a similar situation. The results of this study support the use of both autologous and allogeneic MSC as an efficacious and safe therapeutic option for refractory FCGS.